Sata vuotta hallintolainkäyttövaltaa – Tutkimus korkeimman hallinto-oikeuden ja alueellisten hallinto-oikeuksien valtiosääntöoikeudellisesta asemasta - Pietarinen, Päivi (fi=Turun yliopisto|en=University of Turku|, 2025)
Ensimmäinen hallintotuomioistuin, korkein hallinto-oikeus, perustettiin yhtenä ensimmäisistä itsenäisen Suomen instituutioista vuonna 1918. Korkein hallinto-oikeus oli pitkään ainoa hallintotuomioistuin maassamme, sillä vielä pitkään alemmanasteiset hallinto-oikeudelliset valitusasiat tulivat kuulumaan hallinnon sisällä ratkaistaviksi. Hallintolainkäytön kokonaisuuden institutionalisoituminen vaati pitkän kehityskulun. Vasta vuoden 1989 uudistuksessa lääninoikeuksien voi sanoa saavuttaneen tuomioistuimilta vaadittavan riippumattomuuden. Hallintotuomioistuinjärjestelmän kokonaisuus osana tuomiovallankäytön kokonaisuutta tunnustettiin lopulta vuoden 2000 perustuslaissa. Tässä valtiosääntöoikeuden alaan kuuluvassa väitöskirjassa tutkitaan yhteiskunnallisesti painottuneella oikeusdogmaattisella metodilla hallintolainkäyttövallan institutionalisoitumista, sen sisältöä ja hallintolainkäytön riippumattomuutta montesquieulaisen vallanjaon näkökulmasta. Tutkimuskysymyksiin kuuluu, mitä perustuslainsäätäjä on valtiosäännön tasolla säätänyt hallintotuomioistuimista, niiden asemasta ja tehtävistä sekä hallintolainkäyttövallasta ja vallan rajoista. Lisäksi kysytään mitä toimivaltuuksia ja vaatimuksia valtiosäännöstä ja muusta sääntelystä seuraa suomalaisille hallintotuomioistuimille instituutioina ja hallintolainkäytölle prosessina. Tutkimuksen punaisena lankana on etsiä vastauksia siihen, mitkä ovat hallintotuomioistuinten ja hallintolainkäytön moninaiset funktiot valtiosäännön kokonaisuudessa, ja miten ne näyttäytyvät vallanjaon kokonaisuudessa. Lainkäyttö on merkittävää yhteiskunnallisen vallan käyttöä. Hallintolainkäytössä ratkaistaan yksittäisiä hallintopäätöksiä koskevia oikeuskiistoja ja annetaan yksittäistapauksellista oikeussuojaa. Hallintolainkäytön tehtäväksi on perinteisesti katsottu kuuvan myös hallintotoiminnan laillisuuden varmistaminen ja sitä kautta hallintotoiminnan ohjaaminen. Hallintotuomioistuinten ratkaisuilla on useasti yksittäistä tapausta laajempaa merkitystä viranomaistoiminnassa. Sen vuoksi on olen-naista ymmärtää hallintotuomioistuinten ja hallintolainkäytön valtiosääntöiset tehtävät. Perustuslainsäätäjä on antanut korkeimmalle hallinto-oikeudelle myös muita tehtäviä kuin lainkäyttötehtäviä. Mainitut tuomiovaltaa sivuavat, mutta kuitenkin sen ulkopuolelle asettuvat valtiosääntöiset tehtävät koskevat ensinnäkin alemmanasteisen lainkäytön valvontaa hallintolainkäytön alalla ja toisekseen oikeutta tehdä lain-säädäntöaloitteita. Korkein hallinto-oikeus voi myös antaa lausuntoja lainsäädäntöhankkeista lainvalmistelun kuluessa. Näiden funktioiden myötä korkeimman hallinto-oikeuden tehtävät ovat kansainvälisestikin mitattuna laajat, koska ne eivät rajaudu puhtaaseen lainkäyttövaltaan. Tutkimuskysymyksen ulotan sekä vuoden 1919 hallitusmuotoon että vuoden 2000 perustuslakiin. Näin ollen väitöskirjassa tutkitaan oikeushistoriallisella otteella valtiosäännön ja hallintotuomioistuinten suhdetta mukaan lukien sitä, miten hallintotuomioistuinten valtiosääntöiset tehtävät ovat historian saatossa kehittyneet. Hallintotuomioistuinten muutokset ovat koskeneet hallintotuomioistuinjärjestelmän rakennetta, lainkäytön sisältöä ja sovellettavaa prosessia. Hallintolainkäytössä oikeusturvafunktio on aikojen saatossa korostunut suhteessa julkisen vallankäytön lainalaisuuden varmistamisfunktioon. Alueelliset hallinto-oikeudet ovat vakiinnuttaneet asemansa oikeusturvan takaavina alemmanasteisina tuomioistuimina, jolloin korkeinta hallinto-oikeutta on voitu määrätietoisesti kehittää oikeudenkäyttöä ohjaa-vaksi valituslupatuomioistuimeksi. Valvontafunktio historiallisine tulkintoineen ja käytäntöineen näyttää vahvista-van ja tukevan korkeimmalle hallinto-oikeuden lainkäytön ohjaustehtävää. Siinä ole nähtävissä valtiosääntöisiä hankauskohtia vallanjaon näkökulmasta. Korkeimman hallinto-oikeuden toimivalta tehdä lainsäädäntöaloitteita ja antaa lausuntoja lainsäädäntöhankkeista on näyttäytynyt jossain määrin häilyvämmältä. Vallanjaon näkökulmasta sitä tulisikin käyttää maltillisesti ja tarkkaan harkiten vain niissä kysymyksissä, jotka kuuluvat hallintolainkäyttövallan alaan. Suomen jäsenyydestä Euroopan unionissa tulee tänä vuonna kuluneeksi 30 vuotta. Oikeudellisen ympäristön muuttuminen eurooppaoikeuden myötä (tarkoittaen EU-oikeuden lisäksi myös Euroopan ihmisoikeussopimusta) on heijastunut voi-mallisesti myös hallintolainkäyttöön. Hallintolainkäyttö on eurooppalaistunut ja kansalliset tuomioistuimet käyvät dialogia kansainvälisten tuomioistuinten kanssa. Eurooppalaisen oikeusnormiston soveltamisesta ja oikeuden kansainvälistymisestä on tullut arkipäivää. Se on muokannut kotimaisen hallintolainkäytön valtiosääntöistä roolia. Erityisen ajankohtaista on tuomioistuinten ja tuomareiden riippumattomuus. Oikeusvaltiollisuus ja siihen liittyen tuomiovallankäytön riippumattomuus on joutunut koetukselle useammassakin maassa, myös Euroopassa. Suoranaisia uhkia ei Suomessa ole näköpiirissä, mutta tuomioistuinten ja tuomareiden riippumattomuus on meidänkin oikeuspoliittisessa keskustelussamme ajankohtaisempi kuin koskaan. Vallanjaon kunnioittaminen ja siihen liittyen tuomioistuinten riippumattomuus on yksi oikeusvaltion peruspilareista ja välttämättömistä lähtökohdista. Ilman riippumattomuutta ei ole legitiimiä ja kansalaisten luottamusta nauttivaa tuomioistuinlaitosta. Riippumattomuuden merkitystä oikeusturvalle ja riippumattomuuden eri merkityssisältöjä käsitellään tässä tutkimuksessa aiheen ajankohtaisuuden vuoksi varsin laajasti. Vaikka hallintolainkäytön ja hallintotuomioistuinten valtiosääntöinen status vaikuttaa Suomessa vahvalta, on siinä riippumattomuuden näkökulmasta edelleen korjaamisen paikkoja. Näitä tutkimustuloksia on koottu väitöskirjan loppuun.

A Century of Administrative Justice – A Study on the Constitutional Status of the Supreme Administrative Court of Finland and Regional Administrative Courts Finland’s first administrative court, the Supreme Administrative Court, was established in 1918 as one of the first institutions of the newly independent country. For decades it was the only administrative court in Finland as the administrative appeals at the first instance were to be decided within the administration. The institutionalisation of administrative justice required a long process of development. It was not until the reform 1989 that the lower instances acquired the independent status re-quired of the courts of law. Finally, in the constitutional reform of 2000, the administrative court system was recognised as part of the overall judicial power. This thesis belongs to the field of constitutional law. It uses social legal dogmatics as a methodology to examine the institutionalisation of administrative jurisdiction, the content of administrative jurisdiction and judicial independence from the perspective of Montesquieu’s separation (division) of powers. The research questions include what the constitutional legislator has enacted regarding administrative courts, their role and function and, finally, their powers and the limits of their powers. The leitmotif of the thesis is to identify the multiple functions of administrative courts and administrative justice in the constitutional framework and how the functions are reflected in the overall concept of the separation of powers. The exercise of judicial power is an important exercise of public powers. Ad-ministrative justice resolves individual legal disputes against administrative decisions and provides legal protection in individual cases. Traditionally, administrative justice has also been seen as a means of ensuring the legality of administrative action and thereby guiding administrative action. Decisions of administrative tribunals may extend their impact over an individual case to the decisions of public authorities. The Finnish constitutional legislator has given the Supreme Administrative Court additional functions in addition to justice in administrative matters. These constitutional functions, which are related to the judicial power, but are nevertheless outside it, concern firstly the administration of justice in its own field of competence. Secondly, they concern the right to submit proposals to the Government for the initiation of legislative measures. The Supreme Administrative Court may also issue opinions on bills during the legislative process. The functions of the Supreme Ad-ministrative Court are extensive, even by international comparison. The research questions take as its starting point the first Finnish Constitution Act of 1919 ending to the Constitution of 2000. The study thus takes a legal-historical approach to the relationship between the Constitution and the administrative courts, including the question of how the constitutional functions of the administrative courts have evolved over time. The changes that have affected the administrative courts have concerned the structure of the administrative court system, the administration of justice and the process applied. The function of legal protection of individuals has become more prominent over time than the function of ensuring the legality of administrative action. The regional administrative courts have established themselves as lower courts guaranteeing legal protection, which has allowed the Supreme Administrative Court to develop into a court with a decisive role in guiding the coherence of jurisprudence through precedents. The supervisory function, on the other hand, with its historical interpretations and practices, seems to confirm and support the Supreme Administrative Court's function of guiding the application of the law. There are no constitutional overlaps in terms of the separation of powers. The competence of the Supreme Administrative Court to submit legislative initiatives and to issue opinions on draft laws, has appeared to be somewhat more blurred. From the point of view of the separation of powers, this function should therefore be exercised with moderation and careful con-sideration and be limited to matters falling within the scope of administrative justice. This year marks the 30th anniversary of Finland’s membership of the European Union. The changes in the legal environment brought by European law (meaning not only EU law but also the European Convention on Human Rights) have had a strong impact on the application of administrative justice. Administrative justice has be-come more Europeanised and national courts are in constant dialogue with European and international courts. The application of European law and the internationalisation of law have become commonplace. This has shaped the constitutional role of national administrative justice. The independence of the courts and the impartiality of judges are particularly topical. The rule of law, and with it the independence of the judiciary, has been put to the test in several countries, also in Europe. Fortunately, there are no direct threats on the horizon in Finland, but the independence of courts and judges is more topical than ever in our legal policy debate. Respect for the separation of powers, and hence the independence of the judiciary, is one of the absolute foundations and indispensable prerequisites of the rule of law. Without judicial independence, there can be no legitimate judiciary that enjoys public confidence. The importance of the independence of the judiciary and the numerous definitions of ‘judicial independence’ are dealt with in considerable depth in this study, given their topicality. Although the constitutional position of administrative justice and administrative courts in Finland appears to be strong, there is still room for improvement from the perspective of judicial independence. These findings are summarised at the end of the study

Un siècle de justice administrative : une étude sur les fonctions constitutionnelles de la Cour administrative supreme de Finlande et des cours administratives regionals La première cour administrative de Finlande, la Cour administrative suprême, a été créée en 1918 comme l’une des premières institutions d'un pays récemment devenu indépendant. Pendant des décennies, la Cour administrative suprême a été la seule juridiction administrative du pays, car les recours administratifs en premier ressort étaient, à l'époque, décidés au sein des autorités administratives. L'institutionnali-sation de la justice administrative a exigé un long processus de développement. Ce n'est que depuis la réforme des juridictions administratives régionales en 1989 que ces tribunaux de premier ressort ont acquis un statut indépendant. La réforme cons-titutionnelle de 2000 a finalement reconnu le système des juridictions administra-tives comme faisant partie intégrante du système judiciaire. Cette thèse s'inscrit dans le domaine du droit constitutionnel. J’examine l'institu-tionnalisation de la juridiction administrative, la substance de la juridiction adminis-trative et l'indépendance de l'autorité judiciaire dans une perspective de séparation des pouvoirs, comme l'a indiqué Montesquieu. Les questions de recherche abordées sont les suivantes : Quelles fonctions le législateur constitutionnel accorde-t-il aux juridictions administratives ? Quels sont leur rôle et leur fonction ? Quels sont leurs pouvoirs et leurs limites ? L'objectif de cette thèse est d'identifier les multiples fonc-tions des juridictions administratives et de la justice administrative dans le cadre constitutionnel. L'exercice du pouvoir judiciaire est un élément essentiel du pouvoir d'État. La justice administrative permet de résoudre les recours individuels contre les décisions administratives et offre une protection juridique. Traditionnellement, la justice ad-ministrative est également considérée comme un moyen de garantir la légalité de l'action administrative et donc d'orienter des directions à l’exercice de celle-ci. Les décisions des juridictions administratives ont souvent une portée plus large que celle d'une affaire individuelle. Le législateur constitutionnel finlandais a attribué à la Cour administrative su-prême des fonctions supplémentaires en plus de l'administration de la justice en ma-tière administrative. Ces fonctions constitutionnelles sont liées au pouvoir judiciaire, mais n'en sont néanmoins pas inclues. En premier, la Cour administrative suprême veille à l'administration de la justice dans son domaine de compétence. En deuxième, elle a le droit de soumettre au gouvernement des propositions de prise de mesures en matière législative. La cour peut également, au cours de la procédure législative, émettre des avis sur les projets de loi. Ses fonctions sont étendues et ceci même dans le cadre d'une comparaison internationale. La question de la recherche prend pour point de départ la première loi constitu-tionnelle finlandaise de 1919 pour arriver, finalement, à la Constitution en vigueur depuis 2000. Dans l'étude, une approche historique du droit ainsi que juridique est adoptée concernant la relation entre la Constitution et les juridictions administratives. Les changements qui ayant eu un impact sur les juridictions administratives ont concerné la structure du système juridictionnel administratif, l'administration de la justice ainsi que les éléments procéduraux. Au fil du temps, la fonction de protection juridique des individus est devenue plus importante que la fonction d'assurer la lé-galité de l'action administrative. Les cours administratives régionales se sont impo-sées comme des juridictions de première instance garantissant la protection juri-dique, ce qui a permis à la Cour administrative suprême de se transformer en une cour suprême jouant un rôle décisif dans le maintien de la cohérence de la jurispru-dence par le biais de précédents. La fonction de la veille, quant à elle, avec ses interprétations semble confirmer et soutenir la fonction de la Cour administrative suprême d'assurer l'unité de l'appli-cation du droit. Il n'y a pas de problèmes constitutionnels en termes de séparation des pouvoirs. La compétence de la Cour administrative suprême en matière d'initia-tives législatives et d'avis sur les projets de loi a semblé plus imprécise. D'un point de vue de la séparation des pouvoirs, il convient donc d'exercer cette fonction avec modération et prudence, et de la limiter aux questions relevant de la justice administrative.